Noncooperative Bargaining and Spatial Competition - Bester, Helmut (Econometrica, 1989)
The article develops a bargaining model of spatial competition. Sellers compete by choosing locations in a market region. Consumers face a cost to moving from one place to another. The price of the good is determined as the perfect equilibrium of a bargaining game between seller and buyer. In this game, the buyer has the outside option to move to another seller and so the prices at all stores are interdependent. Existence of a location-price equilibrium is established. The outcome approaches the perfectly-competitive one if the consumer's cost of traveling becomes negligible or if the number of sellers tends to infinity. Copyright 1989 by The Econometric Society.